Proteção miocárdica ao coração hipertrofiado: O eterno desafio - Cressoni, Elthon Silveira [UNESP]; Avanci, Luiz Ernesto; Braile, Domingo Marcolino; Cicogna, Antonio Carlos [UNESP]; Lima-Oliveira, Ana Paula Marques; Gerez, Milena Alonso Egéa; Martins, Antonio Sérgio [UNESP] (FapUNIFESP (SciELO), 2008)
The myocardial protection allowed great advance in cardiac surgery, decreasing the mortality and making more feasible complex surgeries. Latterly, the patient population elected for cardiac procedures has been changing towards elderly patients with ventricular function depressed and myocardial hypertrophy. The myocardial hypertrophy condition represents a great challenge since the beginning of the cardiac surgery. Several techniques have been described to protect the myocardial hypertrophy, however with no satisfactory results. In this manuscript we present the state of the art technique of myocardial protection.
Myocardial protection to the hypertrophied heart: The eternal challenge
Keywords: Cardioplegic solutions; Heart arrest, induced/methods; Hypertrophy, left ventricular; Hypertrophy, right ventricular; cardioplegic agent; heart arrest; heart left ventricle hypertrophy; heart muscle; heart muscle reperfusion; heart right ventricle hypertrophy; human; metabolism; methodology; pathophysiology; reperfusion injury; review; standard; Cardioplegic Solutions; Heart Arrest, Induced; Humans; Hypertrophy, Left Ventricular; Hypertrophy, Right Ventricular; Myocardial Reperfusion; Myocardial Reperfusion Injury; Myocardium